Clinical Characteristics of Patients with Hepatocellular Carcinoma: A Single-Center 3-Year Experience from Somalia - Mohamed A. Hassan-Kadle; Marian Muse Osman; Esra Keles; Hasan Huseyin Eker; Kursad Nuri Baydili; Hussein Mahdi Ahmed; Abdirahman Abdikadir Osman (International Journal of Hepatology)
Background. To evaluate the relationship between prognosticators representing tumor aggressiveness and socio-demographic, laboratory, and imaging findings in patients with hepatocellular carcinoma (HCC). Methods. We retrospectively searched patients with HCC between January 2017 and December 2019 in our tertiary referral hospital. The tumor-related factors and liver damage indicators and their relationship to indicate the value of prognosis were analyzed. Results. A total of 268 HCC patients, with a male-to-female ratio of 2.8 : 1. The mean age was 52.6 years. The patient with portal vein thrombosis (PVT) was older, had higher liver laboratory parameters (AST, ALT, total bilirubin, and direct bilirubin), and had larger tumor size. Patients with the larger tumor size had a higher AFP level, had more tumor multifocality. The majority of patients were in Child’s A (73.6%) and B (17.2%) classes. The laboratory parameters of HCC patients were increased in Child’s C compared to other groups of Child-Pugh classification. Conclusions. The presence of PVT and large-sized tumor in patients with HCC indicated a poorer prognosis than non-PVT group and small tumor sizes.